PENERAPAN METODE BERNYANYI DALAM PENINGKATAN KOSAKATA BAHASA ARAB MUFRADAT - Muh Nur Ilahi; Hasmawati Hasmawati; Sitti Muthmainnah (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This study aims to determine the planning, implementation, and learning outcomes of students in improving Arabic vocabulary through the singing method. This type of research is classroom action research (CAR). The research subjects were 20 Class X IIS MA Pergis Ganra, Soppeng Regency. Data collection techniques used in this study were tests and observations. This study was conducted in two cycles, each cycle consisting of two meetings. The results showed an average score of student vocabulary mastery in cycle I of 74%, with six students not yet reaching the minimum passing grade (KKM), and in cycle II of 89.25%, with all students having reached the minimum passing grade (KKM). These results indicate a 15.25% increase in students' Arabic vocabulary mastery. The improvement in learning outcomes in each cycle shows that the singing method can improve students' Arabic vocabulary.